Urbanization and Income Inequality in Vietnam: An Empirical Investigation at Provincial Level - Do, Quynh Anh; Thi Vi Nguyen; Thi Thanh Duong Nguyen (Thailand and The World Economy, 2024)
The article studies the impact of urbanization on income inequality in Vietnam, using panel data for 63 provinces and cities in the period 2010-2018. The study applies the fixed-effects regression model estimation method with the standard error of (Driscoll & Kraay, 1998) to test the relationship between urbanization and income inequality in Vietnam. Besides, the study also considers this relationship under the influence of human capital. The study has found that urbanization tends to increase income inequality in localities. On the other hand, urbanization can reduce the income inequality between rich and poor under the influence of human capital. Based on the research results, the study has some policy implications for state agencies in realizing the goals of equality and social justice through the process of urbanization, contributing to solutions for the common socio-political stability of the country.